Development and Psychometric Evaluation of the Pediatric Nurse Professional Competence Scale (P-NPCS) for Private Hospitals - Kaur, Gurpreet; Kaur, Sukhbir; Singh, Amandeep (Qualitative and Quantitative Research Center, 2025)
Pediatric nurses require specialized competencies to meet the unique physiological and psychosocial needs of children, yet context-specific assessment tools remain limited in India, particularly for the private healthcare sector. This study aimed to develop and psychometrically validate the Pediatric Nurse Professional Competence Scale (P-NPCS) among nurses in private hospitals in selected districts of Punjab, India. A methodological research design was adopted, involving 385 pediatric nurses recruited through a non-probability, total enumerative sampling method from nine private hospitals. The development process followed a three-phase approach, including item generation based on a literature review, content validation using a three-round Delphi technique with a panel of 20 nursing experts, and scale evaluation through a pilot study and final data collection. The results of the psychometric evaluation using Confirmatory Factor Analysis supported a refined 51-item, ten-factor model with satisfactory fit indices (χ²/df = 2.93, CFI = 0.93, GFI = 0.92, RMSEA = 0.068). The findings further demonstrated high internal consistency, with composite reliability ranging from 0.78 to 0.86 and Average Variance Extracted exceeding 0.50. While 87% of the nurses demonstrated high overall competence, lower scores were identified in the domains of collaboration and professional development. In conclusion, the P-NPCS stands as a robust and reliable instrument for evaluating pediatric nursing competencies within specialized clinical environments. By offering a culturally and contextually validated tool, this study significantly contributes to the field by enabling structured performance evaluations and targeted professional development strategies, ultimately enhancing the quality of pediatric care in the private healthcare sector.